Implementasi Augmented Reality Sebagai Media Promosi Pada Lesehan Kalisari Dengan Metode Based Marker Tracker - Biyas Ola Tafakkur; Lalu Puji Indra Kharisma; Ahmad Ashril Rizal; Abdurahim Abdurahim (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Multimedia, as an information technology product, has the advantage of attracting the imagination and interest of its users. One of the multimedia products whose development is quite widely accepted by most people is augmented reality (AR). With the support of technology, Augmented Reality can combine the real world with the visual world. This study aims to design and build an android-based application using augmented reality technology with the Based Marker Tracker method as an alternative promotional media so that various food/beverage products available at restaurants or Lesehan Kalisari can be more attractive to customers. This application uses Vuforia SDK software, Unity3D with C# programming language, and Blender 3D to create 3D shapes from food/beverage products. This research uses the waterfall development method or what is often referred to as the classic life cycle. This research produces an android-based augmented reality application that can display 3D forms of food/beverage products on the menu list. With this application, it is hoped that it can become an alternative promotional media that increases the number of customers.